THE IMPACT OF HEAVY VEHICLE CHARACTERISTICS ON THE PERFORMANCE AND RESPONSE OF THE PAVEMENT - R. Prasanna Kumar; B. Sudharshan Reddy; R. Madhava Perumal; Vadali Pitchi Raju; CH. Kalyani; S. Priyanka; CH. M. H. Saibaba; N. Selvam (Proceedings on Engineering Sciences)
The pavement reactions brought on by the combined loads that each vehicle's wheels applied were then calculated to determine how much pavement damage each truck had actually done. The significance of environmental, pavement, truck, and tyre elements as influences on pavement deterioration was evaluated by the study. The study's treatment provides a thorough review of the interactions as well as novel insights into the underlying physics, even if the majority of the findings are consistent with the current knowledge of pavement deterioration brought on by heavy vehicle loads. Looking at the results from the standpoint of truck attributes that affect pavement damage as well as pavement and environmental elements that affect sensitivity to truck wheel loads is fascination.